Case series: Diquat poisoning with acute kidney failure, myocardial damage, and rhabdomyolysis - Yu, Guangcai; Wang, Jieru; Jian, Tianzi; Shi, Longke; Zhao, Liwen; Li, Yaqian; Gao, Yikai; Kan, Baotian; Jian, Xiangdong (Frontiers in Public Health, 2022)
Diquat is a herbicide that can have deleterious effects on the kidneys, liver, heart, lungs, and central nervous system on ingestion. Diquat poisoning-associated rhabdomyolysis has rarely been reported. We describe two cases of diquat poisoning with acute renal failure, myocardial damage, and rhabdomyolysis. Case 1: A 17-year-old man experienced anuria after ingesting approximately 200 mL of diquat 16 hours prior. On admission, his creatinine (400 μmol/L), urea (11.7 mmol/L), creatine kinase (2,534 IU/L), and myohemoglobin (4,425 ng/mL) concentrations were elevated. Case 2: An 18-year-old woman who ingested approximately 200 mL of diquat 5.5 hours prior to admission had normal creatinine, urea, and creatine kinase concentrations. Eleven hours after ingestion, she developed anuria with elevated creatinine (169 μmol/L) concentration; her creatine kinase (13,617 IU/L) and myohemoglobin (>3,811 ng/mL) concentrations were remarkably elevated 24 hours after ingestion. Both patients also had elevated aminotransferase and myocardial enzyme concentrations. After undergoing hemoperfusion and hemofiltration, blood diquat concentrations in cases 1 and 2 on admission (16/6 hours after ingestion), after hemoperfusion (20/11 hours after ingestion), and after 8 hours of hemofiltration/8 hours of hemofiltration and 2 hours of hemoperfusion (29/21 hours after ingestion) were 4.9/9.1 μg/mL, 3.4/5.4 μg/mL, and 1.5/1.2 μg/mL, respectively. Severe diquat poisoning can cause acute kidney failure and rhabdomyolysis. Rhabdomyolysis may induce myocardial injury, aggravating kidney damage, and also increase transaminase concentration. Hemoperfusion and hemofiltration could be effective treatments for eliminating diquat in the blood.